The "lifeworld" of Malawian undergraduate student nurses: The challenge of learning in resource poor clinical settings - Gladys Msiska; Pam Smith; Tonks Fawcett (Elsevier, 2014)
Background: In the "lifeworld" of student nurses, the clinical learning experience is indispensable. It plays a vital role in preparing them for their future nursing career. Aim: The aim of the study was to explore the students' perceptions of their clinical learning experience, in view of the problems prevalent in the various clinical settings that are used as teaching hospitals. Design: This was a hermeneutic phenomenological study and the setting was a university nursing college in Malawi. The sample was selected purposively, consisting of thirty participants. Conversational interviews were conducted to obtain participants' accounts of their clinical learning. A framework developed by modifying Colaizzi's procedural steps guided the phenomenological analysis. Findings: The study findings confirm that the clinical learning experience is challenging. There is severe nursing shortage in most clinical settings in Malawi and nursing students appear to be a potential workforce. There is also gross lack of equipment and supplies and sometimes nursing students utilise improvised equipment to perform nursing procedures. This negatively impacts on their learning in the clinical setting. In addition, nursing lecturers do not effectively support students during clinical placements and some nurses are not willing to teach. Conclusion: The study findings portray the problems and challenges which undergraduate nursing students in Malawi encounter during clinical placements. They mainly portray the challenge of learning in resource poor clinical settings.